Evaluasi Kinerja Instalasi Farmasi Rumah Sakit Islam PKU Muhammadiyah Palangka Raya Kalimantan Tengah dengan Pendekatan Balanced Scorecard - Dewi Sari Mulia (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
The Balanced Scorecard translates organizational mission and strategy into operational objectives and performance measures into four perspectives: financial perspective, customer perspective, internal business process perspective, and learning and growth perspective. The results showed that for an economic perspective the value of TOR 13 time, ROI 22% and Profit Margin 18%. From these values, it can be concluded that IFRS financial performance is good enough if it is done by a benchmark towards PKU Muhammadiyah Yogyakarta Hospital and the standards set by the Muhammadiyah LPPK. For the customer perspective obtained from the patient satisfaction survey shows that patients are satisfied with the performance of IFRS. But if it is based on regulations regarding minimum service standards at the Hospital for standard patient satisfaction indicators that must be achieved is 80%, then it can be concluded that the performance of IFRS still needs to be improved. The internal business process perspective for service waiting time indicators shows an average number of 6 minutes for prescription drug and 12 minutes for mixing prescription medication. When compared with the minimum service standards in hospitals for service waiting for time indicators that require a standard ≤ 30 minutes for prescription drug and ≤ 60 minutes for mixing prescription medication, it can be concluded that the performance of PKU Muhammadiyah Palangka Raya IFRS for service waiting time indicators is outstanding. Assessment of the index of drug availability shows a figure of 98%, which means that IFRS still has the challenge of achieving the target level of drug availability of 100%. The learning and growth perspective for employee training indicators shows that 40% of employees received training in 2018.